LYMPHOCYTES IN PATIENTS WITH CHRONIC ACTIVE EPSTEIN-BARR VIRUS INFECTION EXHIBITED ELEVATED PD-1/PD-L1 EXPRESSION AND A PREVAILING TH2 IMMUNE RESPONSE. - kang sun (Mediterranean Journal of Hematology and Infectious Diseases)
Background And Objectives: Chronic active Epstein-Barr virus infection (CAEBV) is a lymphoproliferative disorder characterized by the increased numbers of EBV-infected T/natural killer (NK) cells and ongoing symptoms resembling infectious mononucleosis. Nonetheless, the exact correlation between peripheral lymphocyte subsets and the development of CAEBV remains uncertain. Methods: Consequently, we examined the levels of programmed cell death 1 (PD-1)/programmed death ligand 1 (PD-L1) expression, the status of EBV infection, and the frequencies of peripheral lymphocyte subpopulations in 24 patients with CAEBV and 15 EBV-seronegative donors using flow cytometry.